The Impact of Different Almond Orchard Management Practices in Hyper-Arid Ecosystems on Soil Microbial Communities - Itaii Applebaum; Gil Eshel; Tirza Doniger; Yosef Steinberger (Land, 2025)
The use of service (cover) crops is widely practiced in soil agriculture due to their many benefits, including enhanced nutrient supply and improved soil health. Bacteria, as major decomposers of plant residues in the soil, play essential roles in nutrient cycling. This study examined the impact of various almond orchard management practices on the soil microbial community composition in a hyper-arid ecosystem. High-throughput sequencing was used to compare the microbial communities in two adjacent almond orchards managed with either organic (ORG) or regenerative agriculture (RA) practices, alongside an uncultivated (UC) site. Notably, little is known about the responses of soil bacterial communities in hyper-arid regions to intercrop mulch from service crops. This study may offer insights into the ecological limits of the benefits of service crops in promoting soil health under extreme conditions. Our findings demonstrate that RA management can alter soil organic carbon levels and reshape microbial communities by increasing overall bacterial abundance and enriching specific keystone taxa. These changes may have significant implications for nutrient cycling processes in hyper-arid agroecosystems.